Inventarisasi Tumbuhan Invasif di Komplek Cipadung Permai Kecamatan Cibiru Kota Bandung, Jawa Barat - Habib Indraswara; Hanna Kamillah Suwarna (Jurnal Riset Rumpun Ilmu Tanaman, 2023)
Invasive plants are plants that can reproduce quickly and can pose a threat to biodiversity. An inventory was carried out to determine the types of invasive plants in the Cipadung Permai complex, Cibiru District, Bandung City. Inventory was carried out using a purposive sampling method combined with area exploration. Recording and identification based on relevant sources is carried out. From the results of observations, 14 species from 12 different families were found. Some of the invasive plants found were used by residents as ornamental plants.